Morpho-Physiological Responses of Basil (Ocimum basilicum L.) Microgreens to Chitosan Application and Planting Density - Wei, Frederick Tung Chun; Nakasha, Juju Jaafar; Qazizadah, Ahmad Zubair (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Microgreens are popular culinary ingredients due to their higher nutrient and antioxidant content compared to their mature counterparts. This study was conducted to enhance the seed germination, growth, and yield of basil as a microgreen. The study was divided into two experiments: the first involved basil seeds treated with six chitosan concentrations, including 0, 0.2, 0.4, 0.6, 0.8, and 1% v/v. In the second experiment, the seeds were planted at three densities: 110, 220, and 330 g/m². Based on the results, increasing in concentration of chitosan to an extent led to an increase in seed germination and microgreen growth performances, where 0.6% was the best out of all the treatments as it recorded the highest germination percentage (65%), germination speed (6.918 seeds per day), seed vigour index (4807), seedling height (7.40 cm), root length (3.60 cm), stem diameter (0.56 mm) and leaf area (0.62 cm²). In addition, 220 g/m² was found to be the optimal planting density among the three treatments, due to increased yield and a marketable appearance. Future research is needed to evaluate the nutritional and phytochemical contents.